Literasi Emergen Anak Usia Dini: Studi Kasus di Perpustakaan Daerah Kalimantan Selatan - Irayana, Ika; Assyauqi, Moh Iqbal (Muadalah, 2025)
Emergent literacy is a significant foundation for early childhood literacy development; however, its implementation in non-formal education spaces, such as public libraries, remains a relatively under-researched area. The present study aims to investigate the implementation of the emergent literacy programme at Kids Library KM 6 Banjarmasin Library as an effort to support the development of children's pre-literacy skills. A qualitative approach was adopted, utilising a case study strategy to collect data through participatory observation, in-depth interviews, and documentation. Thematic analysis techniques were employed to analyse the collected data. The findings indicate that the programme has been meticulously conceived and methodically executed through the utilisation of storytelling activities, reading aloud, and the provision of educational play facilities, which collectively foster children's literacy development. Interactions between children, facilitators and the library environment form a holistic literacy experience. The evaluation process remains informal, yet it has been observed to demonstrate children's active engagement and an enhancement in their interest in reading. The findings of this study underscore the significance of fortifying community-based early childhood literacy through the incorporation of play-based methodologies, multisensory media, and the pivotal role of librarians as facilitators. The findings of this study make theoretical and practical contributions to the development of early childhood literacy policies and services in non-formal education institutions.